The research trends of music general education: A bibliometric review - Li, Rui; Kamaruzaman, Fathiyah Mohd; Nasri, Nurfaradilla Mohamad (Edelweiss Applied Science and Technology, 2025)
Music general education encompasses various learning methods, including sensory engagement, appreciation, experience, and creation. It leverages music's unique auditory experiences and aesthetic values to cultivate and develop students' musical literacy, imagination, and creativity. However, within the educational system, music general education is often undervalued, leading to a mismatch between its development and its actual educational significance. Despite increasing research interest in this field, a systematic, layered, and focused review and analysis are still necessary. This study employed bibliometric methods to analyze publications from the Web of Science database using VOSviewer. It conducted descriptive statistical analyses on publication quantities, citation trends, highly cited articles, the top 10 journals, countries, and organizations. Additionally, a visual network map analysis was performed on keyword co-occurrence, as well as on countries and organizations based on co-authorship. The results identified the most influential articles, journals, countries, and organizations from 2014 to 2024. The study also mapped the collaborative relationships between different countries and organizations and revealed research hotspots and thematic evolution within this field. These findings provide valuable insights for future research directions and potential collaborative opportunities in the domain of music general education.